(untitled) (Journal of the College of Basic Education, 2022)
Praise is to the world’s flight, and prayers and peace be upon the best of His creation, our master Muhammad, and upon the pure and good God. The character is an important narrative component, therefore, the choice of studying the personality and its patterns came in the novel of swatiq AL- Quloubi " the Iraq novelist, I naam Jajj, The research. In cluded the concept of personality in Arab and western criticism, then included personality patterns in the novel, and in cluded studying the impact of space and time and its relationship to personality, finally, the search we carried out with conclusion in which the most important search results were recorded.